2023
DOI: 10.17507/jltr.1405.31
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Implications in EFL Classrooms: A Reflective Praxis of Vocabulary Strategies and Techniques

Sohaib Alam

Abstract: Teaching vocabulary is a challenging ordeal, not only because of the vastness of vocabulary but also because it takes much effort to enable the students to acquire the meaning with their correct usage. The study uses qualitative research to elaborate strategies that can be implemented in EFL classrooms to teach vocabulary-based content. The present study has highlighted the meaning of reflective praxis in the teaching-learning process and how the process of reflection ultimately has a desirable impact on both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…In this regard, the results of the studies [52], [53], [55], [57], [58] are in line with the objective of improving language skills. These studies demonstrated how morphological-based activities can be used to enhance language [55], [56], [57], [58], [59], [60], [61], [62], [63]. The integration of SNS in classroom pedagogy can serve as a catalyst for addressing writing errors effectively, provided that it is used in a controlled manner by the instructors [64].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard, the results of the studies [52], [53], [55], [57], [58] are in line with the objective of improving language skills. These studies demonstrated how morphological-based activities can be used to enhance language [55], [56], [57], [58], [59], [60], [61], [62], [63]. The integration of SNS in classroom pedagogy can serve as a catalyst for addressing writing errors effectively, provided that it is used in a controlled manner by the instructors [64].…”
Section: Discussionmentioning
confidence: 97%
“…These included the likelihood of the platform acting as a source of distraction and a decrease in user engagement towards the end of the study. These instances illustrate that while some learners may be enthusiastic about integrating SNSs within the ESL classroom, others may have reservations and exhibit caution regarding their implementation in an academic context [60].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These observations underscore the role of the learner's first language in inflectional morpheme error patterns in ESL contexts. Moreover, numerous research supports the idea of using different sorts of practical eclectic praxis can be used to curtail errors of students in real life contexts (Alam et al, 2022;Alam et al, 2020;Alam, 2022;Alam, 2023;Mahant et al, 2023). Productive skills of language like writing needs real life practice which can only be provided through communicative strategies or activities that can provides platforms to students to practice language skills .…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study hold practical significance for teaching second languages by shedding light on what needs to be taught and effective learning techniques. The study also foregrounds the challenges and issues of today's classroom pedagogy as well as to grasp the nuances of English language as lingua franca (Alam, 2023;.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, 11 students commented that vocabulary is pivotal to travel to other countries and understand foreign people. Alam (2023), says that productive vocabulary is the words that students can comprehend and pronounce accurately such as speaking and writing in a proper and correct time, for that is essential students expand their vocabulary terms to use and distinguish them from basic vocabulary while they are speaking and writing. Improving productive skills means that students will emphasize learning new words and terms to improve their understanding, facilitating their communication skills to share their ideas and thoughts more effectively to achieve success.…”
Section: Instrumentmentioning
confidence: 99%